Implementation Of An Internet Of Things (IoT)-Based Indoor Air Quality Monitoring System: A Case Study Of PT. Bianglala Metropolitan - Muhammad Dimas Pramudya Anugrah Pratama Dimas; Rinna Rachmatika (International Journal of Health Engineering and Technology, 2026)
This research aims to develop an indoor air quality monitoring system using the ESP32-S3 equipped with gas, temperature, and humidity sensors. The introduction discusses the background of indoor air quality issues and the importance of real-time monitoring. The research objective is to design and implement a prototype device capable of efficiently detecting and monitoring air quality parameters. The methodology involves developing a prototype device by integrating gas, temperature, and humidity sensors into the ESP32-S3. Subsequently, testing is conducted to evaluate the prototype's performance in measuring and monitoring air quality indoors. The results indicate that the prototype successfully measures and monitors gas concentration, temperature, and humidity accurately. Monitoring data can be accessed in real-time through applications or web-based platforms. These findings suggest that the development of this system can be an effective solution for indoor air quality monitoring in various enclosed spaces. The conclusion of this research states that the implementation of gas, temperature, and humidity sensors in the development of an indoor air quality monitoring system using the ESP32-S3 has successfully achieved its intended goals. This system can serve as a foundation for further development to enhance monitoring and control of air quality in various indoor environments.